Optimal Vitamin D Status: A Critical Analysis on the Basis of Evidence-Based Medicine - Bouillon, Roger; Van Schoor, Natasja M.; Gielen, Evelien; Boonen, Steven; Mathieu, Chantal; Vanderschueren, Dirk; Lips, Paul (The journal of clinical endocrinology and metabolism, 2013)
Context:Public health authorities around the world recommend widely variable supplementation strategies for adults, whereas several professional organizations, including The Endocrine Society, recommend higher supplementation.Methods:We analyzed published randomized controlled clinical trials to define the optimal intake or vitamin D status for bone and extraskeletal health.Conclusions:The extraskeletal effects of vitamin D are plausible as based on preclinical data and observational studies. However, apart from the beneficial effects of 800 IU/d of vitamin D3 for reduction of falls in the elderly, causality remains yet unproven in randomized controlled trials (RCTs). The greatest risk for cancer, infections, cardiovascular and metabolic diseases is associated with 25-hydroxyvitamin D (25OHD) levels below 20 ng/mL. There is ample evidence from RCTs that calcium and bone homeostasis, estimated from serum 1,25-dihydroxyvitamin D and PTH, calcium absorption, or bone mass, can be normalized by 25OHD levels above 20 ng/mL. Moreover, vitamin D supplementation (800 IU/d) in combination with calcium can reduce fracture incidence by about 20%. Such a dose will bring serum levels of 25OHD above 20 ng/mL in nearly all postmenopausal women. Based on calculations of the metabolic clearance of 25OHD, a daily intake of 500–700 IU of vitamin D3 is sufficient to maintain serum 25OHD levels of 20 ng/mL. Therefore, the recommendations for a daily intake of 1500–2000 IU/d or serum 25OHD levels of 30 ng or higher for all adults or elderly subjects, as suggested by The Endocrine Society Task Force, are premature. Fortunately, ongoing RCTs will help to guide us to solve this important public health question.